Shear Behaviors of the Intersurface between Rice Straw Rope and Dredger Fill Silt: Experimental and Mechanism Studies - Guizhong Xu; Ji Chen; Shenjie Shi; Angran Tian; Qiang Tang (Advances in Civil Engineering)
The further development of land reclamation, port waterway, and wharf construction brings about proper treatments of dredger fill silt, while huge amounts of rice straw set aside in China argument rational disposal every year. Therefore, rice straw is bundled up as ropes, which represent as drainage body and reinforcement, to make eco-friendly treatment for dredger fill silt. This paper investigates the mechanical properties and validity of rice straw rope as certain treating material of dredger fill silt through a series of pull-out test, mass loss test, and tension test on specimens with different water contents and dry densities. The results reveal that peak value of interfacial shear strength rises with the increase of normal stress at the same immersion time, and in particular, it rises by up to 250.0% when the normal stress is 40 kPa. The tensile force of rice straw rope increases slowly with the rise of tensile displacement, and the failure mode changes from brittle to ductile with the rise of immersion time, which witnesses first rapid back slow degradation trend. The proper interfacial shear strength, tensile force, and reasonable degradation rate of rice straw rope make it ideal in drainage and consolidation of dredger fill silt.